Interaction Diagrams for Reinforced Concrete Hollow Circular Cross-section (Proceedings of Faculty of Civil Engineering, 2019)
The procedure for creating interaction diagrams for reinforced-concrete hollow circular cross sections, based on HRN EN 1992-1-1, is described in the paper. Due to introduction of new concrete strength classes, with somewhat different parameters for the stress-relative strain diagram, it has become necessary to develop new interaction diagrams. The computation procedure, based on which hollow circular cross section interaction diagrams were made for concrete classes from C12/15 to C50/60, was conducted. The use of these interaction diagrams will simplify dimensioning of reinforced-concrete hollow circular cross-sections.
Keywords: reinforced concrete; dimensioning; hollow circular cross-section; interaction diagrams